2017
DOI: 10.1097/igc.0000000000000948
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node and Ovarian Tumors: A Series of 20 Patients

Abstract: In patients with ovarian tumor(s), the detection of sentinel nodes is feasible. They are located in different anatomic areas both ipsilaterally and contralaterally, although most of them are found in the para-aortic region. The reliability of the sentinel node concept should be evaluated in the framework of a multicenter trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 9 publications
2
24
0
8
Order By: Relevance
“…Few studies have described a feasible approach to sentinel node mapping in patients with ovarian cancer. [16][17][18][19][20][21] Unlike vulvar, cervix, and endometrial cancer, where the injection site is readily accessible before surgical prepping, the ovary is much more difficult to access. Among the challenges of where, when, and what to inject, is the equally inconvenient procedural step of needing to remove the clinically suspicious ovary before confirming that it has a malignancy, prompting the need to perform sentinel node mapping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have described a feasible approach to sentinel node mapping in patients with ovarian cancer. [16][17][18][19][20][21] Unlike vulvar, cervix, and endometrial cancer, where the injection site is readily accessible before surgical prepping, the ovary is much more difficult to access. Among the challenges of where, when, and what to inject, is the equally inconvenient procedural step of needing to remove the clinically suspicious ovary before confirming that it has a malignancy, prompting the need to perform sentinel node mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the technical complexity and risk of tumor dissemination associated with the injection of tracers into the cortex 16 17 have limited the published experience to few studies with a small sample of patients, most not involving malignant ovarian tumors. [16][17][18][19][20][21][22][23] The objective of this study was to prospectively delineate any major safety concerns related to our proposed sentinel lymph node technique and assess its feasibility in patients with clinical stage I-II ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have evaluated the feasibility of detecting SLNs by injecting tracer(s) into the mesovarium and/or ovarian ligaments. Tracer injection prior to tumor resection and examination by frozen sections resulted in very high detection rates (87.5-100%) of at least one SLN (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) . The present study showed that injection of tracer into the remains of both ovarian ligaments after resection of the pathological adnex resulted in a low rate of SLN detection (3 out of 11 patients, 27%; CI 10-53%).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the feasibility of the SLN technique in patients with early-stage EOC (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) . Most recent studies utilized a method in which a tracer is injected into the ovarian ligaments prior to tumor resection, with nearly all of these studies reporting very high detection rates (71-100%…”
Section: Introductionmentioning
confidence: 99%
“…W e have read with great interest the article of Nyberg et al, 1 which was recently published in the International Journal of Gynecological Cancer. They reported the results of lymphatic mapping and sentinel node biopsy in 20 patients with ovarian tumors and concluded that sentinel node biopsy is feasible in these tumors.…”
mentioning
confidence: 99%